Optimization of Donor Lymphocyte Infusion for AML Relapse After Allo-HCT in the Era of New Drugs and Cell Engineering - Ye, Yishan; Yang, Luxin; Yuan, Xiaolin; Huang, He; Luo, Yi (Frontiers in Oncology, 2022)
Donor lymphocyte infusion (DLI) is a key strategy for the treatment of AML relapse after allogeneic hematopoietic cell transplantation (allo-HCT), and has been used either prophylactic, pre-emptive or therapeutic. However, prognosis of these patients remains dismal even after DLI infusion (2-year OS ~25%), and the efficacy is achieved at the cost of toxicities such as graft-versus-host disease (GVHD). Attempts to optimize DLI efficacy and safety such as dose/timing modification and use of cytoreduction before DLI have been performed previously. Recently, great number of novel targeted and immunomodulatory agents have emerged. Some of them, such as hypomethylating agents, FLT3 and Bcl-2 inhibitors, have been used in combination with DLI aiming to enhance the graft-versus-leukemia (GVL) effect. Moreover, manipulation of the DLI graft through cell selection (e.g donor NK cells) or cell engineering (donor CAR-T cells) have shown potentially superior anti-tumor effects but less GVH effect than conventional DLI in clinical trials. This review summarizes the recent advances on the use of DLI for the prophylaxis/treatment of AML relapse, and discuss the future strategies which may further improve the treatment efficacy.